(NkRIM)QÆNALXNO(B-(NPROCESUALXNE PRAWO (B:s)E (NKURS LEKC)QÆJ (B/s)E - (NlOBOJKO(B, (Nl(B. (Nm(B.,s ((NkI)QÇW (B:s)E )Qæ(NSTINA(B,s)E, 2005)
(NwIKLADENO OSNOWN)QÆ PONQTTQ KRIMÆNALXNO(B-(NPROCESUALXNOÇ NAUKI TA PROBLEMI PRAKTIKI ZASTOSUWANNQ NORM KRIMÆNALXNO(B-(NPROCESUALXNOGO PRAWA ORGANAMI DÆZNANNQs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpRAWOs -- (NkRIM)QÆNALXNE PRAWOs)E; (NKRIM)QÆNALXNIJ PROCESs)E; (NPRAWOs; (NZAKONs; (NDOKAZIs; (NDOKAZUWANNQs; (NSL)QÆDSTWOs)E; (NOBWINUWA^ENIJs; (NP)QÆDSUDNÆSTXs)E; (NSUDs; (NAPELQC)QÆQs)E; (NWIROKs; (NR)QÆ[ENNQs)E; (NPROTOKOLs